2015
DOI: 10.1177/1098612x14565497
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of rapidly growing mycobacteria isolated from Australian cats to ivermectin, moxidectin, ceftiofur and florfenicol

Abstract: All drugs appear to have no efficacy in vitro for the treatment of RGM infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…There are reports from different parts of the world of mycobacteriosis in cats indicating a prevalence of M. fortuitum as the etiologic agent. Usually, cats present skin infections in the form of non-healing ulcerative pyogranulomatous dermatitis and panniculitis [7][8][9][10][11]. In other animals, such as cattle, M. fortuitum can cause chronic mastitis [12].…”
Section: Introductionmentioning
confidence: 99%
“…There are reports from different parts of the world of mycobacteriosis in cats indicating a prevalence of M. fortuitum as the etiologic agent. Usually, cats present skin infections in the form of non-healing ulcerative pyogranulomatous dermatitis and panniculitis [7][8][9][10][11]. In other animals, such as cattle, M. fortuitum can cause chronic mastitis [12].…”
Section: Introductionmentioning
confidence: 99%
“…A few years later,Lim et al (2013) examined the antibacterial effect of four avermectins (doramectin, ivermectin, MOX and selamectin) and found no inhibitory effect on the bacteria Escherichia coli, Acinetobacter baumannii, Pseudomonas aeruginosa, Streptomyces lividans, Kocuria rhizophila, and Staphylococcus aureus. However, there was reported evidence that MOX may inhibit the growth of Mycobacterium tuberculosis(Lim et al, 2013)d ulcerans(Omansen et al, 2015) which is desirable, but not of other rapidly growing mycobacteria(Woerde et al, 2015). Our results indicate that MOX is inactive against cultivable soil microorganisms.…”
mentioning
confidence: 53%
“…. Macrocyclic lactones, such as MOX, are considered effective against helminths and may affect insects and arachnids, but they are considered inactive against annelids, bacteria and fungi(Lim et al, 2013;Halley et al, 1989b; Kolmann et al, 2004;Woerde et al, 2015). An early study showed that concentrations of 10 − 8 to 10 − 3 moles of pure ivermectin in growth broth affected the reproduction and development of some lamentous fungi but not others(Kollmann et al, 2004).…”
mentioning
confidence: 99%
“…On the other hand, the presence of MOX in the faeces did not affect the CFU of fungi and bacteria in the growth media ( Table 3 ). Macrocyclic lactones, such as MOX, are considered effective against helminths and may affect insects and arachnids, but they are considered inactive against annelids, bacteria, and fungi [ 23 , 25 , 49 , 50 ]. An early study showed that concentrations of 10 −8 to 10 −3 M of pure ivermectin in growth broth affected the reproduction and development of some filamentous fungi but not others [ 49 ].…”
Section: Discussionmentioning
confidence: 99%